Efficacy of systemic therapies in men with metastatic castration resistant prostate cancer harboring germline ATM versus BRCA2 mutations. Issue 16 (13th September 2021) - Sokolova, Alexandra O.; Marshall, Catherine H.; Lozano, Rebeca; Gulati, Roman; Ledet, Elisa M.; De Sarkar, Navonil; Grivas, Petros; Higano, Celestia S.; Montgomery, Bruce; Nelson, Peter S.; Olmos, David; Sokolov, Vadim; et al.
Abstract: Background: Among men with metastatic prostate cancer, about 10% have germline alterations in DNA damage response genes. Most studies have examined BRCA2 alone or an aggregate of BRCA1/2 and ATM . Emerging data suggest that ATM mutations may have distinct biology and warrant individual evaluation. The objective of this study is to determine whether response to prostate cancer systemic therapies differs between men with germline mutations in ATM (g ATM) and BRCA2 (g BRCA2) . Methods: This is an international multicenter retrospective matched cohort study of men with prostate cancer harboring g ATM or g BRCA2 . PSA50 response (≥50% decline in prostate‐specific antigen) was compared using Fisher's exact test. Results and Limitations: The study included 45 g ATM and 45 g BRCA2 patients, matched on stage and year of germline testing. Patients with g ATM and g BRCA2 had similar age, Gleason grade, and PSA at diagnosis. We did not observe differences in PSA50 responses to abiraterone, enzalutamide, or docetaxel in metastatic castration resistant prostate cancer between the two groups; however, 0/7 with g ATM and 12/14 with g BRCA2 achieved PSA50 response to PARPi ( p < .001). Median (95% confidence interval) overall survival from diagnosis to death was 10.9 years (9.5‐not reached) versus 9.9 years (7.1‐not reached, p = .07) for the g ATM and g BRCA2 cohorts, respectively. Limitations include the retrospective design and lack of mutation zygosity data. Conclusions: Conventional therapies can be effective in g ATM carriers and should be considered before PARPi, which shows limited efficacy in this group. Men with g ATM mutations warrant prioritization for novel treatment strategies.